Health professionals directly involved in the diagnosis, treatment, and care of patients with Covid-19 - Rolim Neto, Modesto Leite (Avanços em Medicina, 2025)
Introduction: Health professionals directly involved in the diagnosis, treatment, and care of patients with COVID-19 develop the insertion of psychic spaces for the installation of pain and psychological suffering and other mental health symptoms. Objective: Carry out a analysis of the psychiatric repercussions based people on the front lines: Nurses, doctors, healthcare workers, and other medical professionals who are testing for and treating patients with COVID-19 Method: This current literature review has utilized literature reserves and scientific search engines MEDLINE, EMBASE and Web of Science. The search terms included, “SARS-CoV-2”, “Mental Health,” “psychiatric repercussions”, "People on the front lines " “COVID-19”. Specific choices of unique papers from each of the searches were identified. The inclusion criteria were relevance and availability of full-text. Papers were excluded on the basis of relevance and non-availability of full-text. Papers were identified in the general literature reserve as pertinent to the search terms. Results: Work-related stress is a potential cause of concern for health professionals. Conclusion: Evidence highlights some timely mental health care that needs to be developed urgently, such as: use of psychotropic drugs; specialized psychiatric treatments and appropriate mental; and health status updates for professionals in the Intensive Care Unit; psychological counseling; and psychotherapy techniques such as those based on the stress adaptation model.